1996
DOI: 10.1016/0304-3959(96)03083-7
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile threshold is elevated in temporomandibular disorders

Abstract: Experimental pain can elevate vibrotactile threshold, a phenomenon attributed in the literature to the operation of a 'touch gate.' It is not known, however, whether clinical pain produces similar effects. To explore this possibility, we measured vibrotactile threshold in patients with temporomandibular disorders (TMD) whose pain had a prominent myalgic component. Two-interval forced-choice tracking was used to determine threshold for a 25-Hz vibratory stimulus presented on the cheek. Threshold was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 37 publications
2
27
2
Order By: Relevance
“…Using the adaptation protocol of Hollins et al (1996), there was a main effect of the block of 20 trials (corresponding to pre-adaptation, adaptation, or post-adaptation phases), with thresholds increasing during the adaptation phase, as expected (F = 51.41; p < 0.0001, Fig. 3B).…”
Section: Vibrotactile Adaptationsupporting
confidence: 78%
See 1 more Smart Citation
“…Using the adaptation protocol of Hollins et al (1996), there was a main effect of the block of 20 trials (corresponding to pre-adaptation, adaptation, or post-adaptation phases), with thresholds increasing during the adaptation phase, as expected (F = 51.41; p < 0.0001, Fig. 3B).…”
Section: Vibrotactile Adaptationsupporting
confidence: 78%
“…In Experiment 1, we tested participants' ability to detect constant pressure using thin nylon, "von Frey" filaments. Since another possibility for hypersensitivity in autism is that sensory neurons fail to adapt normally, we measured adaptation to the detection of vibrotactile stimuli in Experiment 2, using a paradigm known to produce adaptation in non-autistic participants (Hollins, Sigurdsson, Fillingim, & Goble, 1996). In Experiment 3, we obtained magnitude estimates for the perceived hedonic value (pleasantness/unpleasantness) of textured surfaces; in Experiment 4, we measured thresholds for thermal sensations of cool and warmth, and in Experiment 5, we obtained thermal pain thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased vibration detection threshold (ie, less sensitivity) has been demonstrated in knee OA, 53 hip OA, 55 and temporomandibular joint disorders. 26 It has been proposed that vibration detection threshold may be an indicator of aberrant joint proprioception and, consequently, joint pathology 56 ; however, proprioception was not assessed in this study. Interestingly, a subsequent study found a correlation between improvement in pain and improvement in proprioception in persons with knee OA.…”
Section: Quantitative Sensory Testingmentioning
confidence: 79%
“…1 While both of these studies investigated cutaneous pain, hypoesthesia has been demonstrated in subjects with experimentally induced muscle pain 65 and in individuals with chronic musculoskeletal dysfunction, in particular, temporomandibular joint dysfunction. 26 The mechanisms behind these findings require further clarification. Nonetheless, clinical findings of hypoesthesia, dysesthesia, and/ or mechanical allodynia in the region of a chronic musculoskeletal condition are suggestive of altered central nociceptive mechanisms.…”
Section: Pain-associated Hypoesthesia and Allodyniamentioning
confidence: 99%
See 1 more Smart Citation